Effects of Coral Sand Powder on the Strength and Durability Properties of Crushed Limestone Aggregate Concrete - Jesse Pereso Oloimutie; Peter Kavita Nzimbi (Advances in Materials Science and Engineering)
This study explores the impact of coral sand powder (CSP) on the mechanical and durability properties of crushed limestone aggregate concrete (CLAC). The investigation aimed to improve the strength and durability of CLAC, which is typically limited by the weak and permeable nature of crushed limestone aggregates. The research involved using different proportions of CSP (0%, 3%, 6%, 9%, 12%, and 15%) as a mineral admixture. The research paper embarks on an in-depth analysis of incorporating CSP as a supplementary cementitious material (SCM) in CLAC, with a specific focus on enhancing its strength and durability properties. Traditional crushed limestone aggregates tend to exhibit weaknesses and high permeability, presenting limitations in the robustness and longevity of the resultant concrete structures. The study derives a multitude of insights from various individual research efforts, demonstrating that CSP can significantly improve these properties by enhancing compressive strength, refining pore structure, and enhancing overall durability. These improvements are largely attributed to the pozzolanic activity of CSP. The observed high brittleness of limestone aggregate reduces the strength and stiffness of the concrete. X-ray diffraction fluorescence was used in the chemical characterization of cement and CSP. Quantitative analysis led to the conclusion that 6% CSP as an additive is optimal for the enhancement of concrete properties such as compressive and tensile strengths, water absorption capacity, and resistance to sulfate attack. Techniques such as scanning electron microscope (SEM) analysis and energy-dispersive X-ray spectroscopy (EDS) were carried out to show the concrete matrix and interfacial transition zone. The results of this study showed promising optimization of concrete mixtures for enhanced performance, sustainability, and durability of concrete structures and offered a perspective on material innovation in concrete production, thus making use of the abundant and renewable coral sand in local construction projects.